2009
DOI: 10.1007/s11664-009-0872-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Aging on Impact Absorbed Energies of Solder Joints Under High-Strain-Rate Conditions

Abstract: This study was concerned with the effect of thermal aging on the impact properties of solder joints. Three kinds of solders, conventional Sn-37Pb solder, Sn-3.8Ag-0.7Cu solder, and Sn-3.8Ag-0.7Cu doped with rare-earth (RE) elements, were selected to manufacture joint specimens for the Charpy impact test. U-notch specimens were adopted and isothermally aged at 150°C for 100 h and 1000 h, and then impacted by using a pendulum-type impact tester at room temperature. The Sn-37Pb solder joints exhibited higher perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…The previous research reported that the solidification cooling rate affected both microstructure and mechanical behavior of solder alloys significantly [15][16][17]. Additionally, a high-strain-rate test demonstrated that annealing Sn-Ag-Cu solder joints at 150 1C for 100 h increased the impact toughness due to the coarsened [18]. Accordingly, the microstructure and the mechanical properties of solder joints can be controlled by various heat treatment.…”
Section: Introductionmentioning
confidence: 98%
“…The previous research reported that the solidification cooling rate affected both microstructure and mechanical behavior of solder alloys significantly [15][16][17]. Additionally, a high-strain-rate test demonstrated that annealing Sn-Ag-Cu solder joints at 150 1C for 100 h increased the impact toughness due to the coarsened [18]. Accordingly, the microstructure and the mechanical properties of solder joints can be controlled by various heat treatment.…”
Section: Introductionmentioning
confidence: 98%